Model Challenge Based Learning berbasis Kahoot: Strategi Meningkatkan Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran IPA Kelas IV Sekolah Dasar - Kusumaningtyas, Nanda Hamidah; Rusnilawati, Rusnilawati (PAKAR Pendidikan, 2025)
This research aims to assess the degree to which the paradigm of challenge-based learning in conjunction with interactive media, such as Kahoot, influences students' critical thinking skills. Students in the fourth grade at Kradenan State Elementary School who utilize Kahoot interactive media to develop their critical thinking abilities make up the study's population. This research used a quasi-experimental technique using non-equivalent control groups and a quantitative approach. A study sample consisted of two classes, namely class IV of Kradenan State Elementary School, which served as an experimental class with n = 17. As an experimental class, Kradenan State Elementary School had 17 students using the Challenge Learning approach with the use of Kahoot interactive media. In comparison, the control group also had 17 students using Cooperative Learning. A description question that incorporates elements of critical thinking via validity and reliability testing serves as the research tool, via the findings of validity and reliability tests. The findings of the investigation demonstrated that the two classes' critical thinking abilities differed significantly in a good way. Using Kahoot interactive media, the challenge model-based learning model is used. It has a significant impact on pupils' critical thinking abilities. Students' critical thinking abilities. The N-Gain test analysis findings, which revealed 69% (from 56-75%), demonstrate this. The study's findings demonstrate how well the Challenge Learning approach, combined with Kahoot media, enhances foundational education by fostering teamwork, learning dynamics, and students' capacity for critical thinking